Low-Level Laser Therapy Attenuates the Myeloperoxidase Activity and Inflammatory Mediator Generation in Lung Inflammation Induced By Gut Ischemia and Reperfusion: A Dose-Response Study - Mafra- de- Lima, Flávia; Aimbire, Flávio; Miranda, Humberto; de Paula Vieira, Rodolfo; Ligeiro de Oiveira, Ana Paula; Albertini, Regiane (Journal of Lasers in Medical Sciences, 2014)
Introduction: Intestinal ischemia and reperfusion (i-I/R) is an insult associated with acute respiratory distress syndrome (ARDS). Herein we evaluate the dose-response effect of low-level laser therapy (LLLT) on lung inflammation induced by i-I/R. Methods: Mice were subjected to mesenteric artery occlusion (45 min) and killed after clamp release and intestinal reperfusion (2h). Increasing doses (1, 3, 5 and 7,5 J/cm2) of laser irradiation (660 nm) was carried out on the mice skin over the upper bronchus for 5 min after initiating reperfusion. Neutrophils activation was determined by myeloperoxidase (MPO) activity. The mRNA expression and protein concentration of inflammatory mediators IL-1β, IL-6, TNF and IL-10 in lung were measured by RT-PCR and ELISA, respectively. Results: With exception of 1J/cm2, LLLT reduced MPO activity as well as IL-1β levels in the lungs from inflamed mice. LLLT was also markedly effective in reducing both IL-6 and TNF expression and levels in the lungs from mice submitted to i-I/R in all laser doses studied. Otherwise, LLLT significantly increased the protein levels of IL-10 in inflamed mice by i-I/R; however only in the dose of 1J/cm2. Conclusion: We conclude that the LLLT is able to control the neutrophils activation and pro-inflammatory cytokines release into the lungs in a model of i-I/R in mice.